SPEKTROSKOPI INFRAMERAH SENYAWA KALSIUM FOSFAT HASIL PRESIPITASI - Soejoko, Djarwani S.; Wahyuni, Sri (UI Scholars Hub, 2002)
Infrared Spectroscopy of Precipitated Calcium Phosphate Compound. Samples of calcium phosphate compounds were produced from saturated solutions containing of calcium and phosphate ions. The experiments were carried out using solutions at temperature 25 º C and 70 º C, combined with different pH value of 5, 7, 9 and 11. Precipitation mass from solutions at 70 º C was relatively higher compare to that produced from solutions at 25 º C. It was also shown that generally the mass precipitation rose with the increasing of pH. Sample analyses were performed with the use of infrared spectroscopy, particularly for the samples produced from solutions at 70 º C. Based on the ν4 phosphate absorption band, it was indicated that apatite crystals found in most samples which its amount gave rise to the increasing of pH. Infrared spectroscopy of the heated samples produced with pH 11 showed that water molecules could be present either at the surface of crystals or trapped in the crystal structure.